PEMANFAATAN TIK SEBAGAI MEDIA PEMBELAJARAN BAGI GURU SMA DI KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Mananggel, Marlin B; Moma, La; Laamena, Christina M (Universitas Pattimura, 2021)
The current problem is that teachers are not capable to adapt to the development of education based of tecnology. Teachers are not entirely literate in information and communication technology. The purpose of this program is to train teachers in utilizing information and communication technology as a medium of learning. This program was implemented at SMA Negeri 22 Seram Barat, Hatusua Village, Kairatu District, West Seram Regency as partners and the target audience were high school teachers throughout Kairatu District. This program is carried out in several stages, namely planning, implementation, evaluation and reflection. At the planning stage, coordination is carried out with partners, then the date of the activity is set. The implementation phase consists of training, demonstration and practice. The evaluation stage is carried out directly by the implementer, namely filling out questionnaires by participants. The results of the questionnaire show that this training activity is considered very good with an average value of 4.85 and there are suggestions that such activities should be sustainable and present more interesting material. While the reflection stage is carried out jointly between the implementer and the participants (partner teachers). This program is expected to increase the mastery of partner teachers on information and communication technology as a learning medium and will continue and develop not only in Kairatu District, but also for teachers throughout West Seram Regency